2018
DOI: 10.1038/s41598-018-21505-8
|View full text |Cite
|
Sign up to set email alerts
|

A genetic variant in SLC30A2 causes breast dysfunction during lactation by inducing ER stress, oxidative stress and epithelial barrier defects

Abstract: SLC30A2 encodes a zinc (Zn) transporter (ZnT2) that imports Zn into vesicles in highly-specialized secretory cells. Numerous mutations and non-synonymous variants in ZnT2 have been reported in humans and in breastfeeding women; ZnT2 variants are associated with abnormally low milk Zn levels and can lead to severe infantile Zn deficiency. However, ZnT2-null mice have profound defects in mammary epithelial cell (MEC) polarity and vesicle secretion, indicating that normal ZnT2 function is critical for MEC functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 77 publications
1
20
0
1
Order By: Relevance
“…Women harboring T 288 S, the most common variant we previously identified (16% frequency) 23 , had biomarkers of oxidative and ER stress evident in their breast milk 29 and an elevated milk Na/K ratio 23 , strongly suggesting breast dysfunction. In vitro studies determined T 288 S is mislocalized to the ER and lysosomes, and leads to accumulation of ER and lysosomal zinc, and activation of STAT3 signaling; however, the molecular and clinical implications of these observations are not currently understood.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Women harboring T 288 S, the most common variant we previously identified (16% frequency) 23 , had biomarkers of oxidative and ER stress evident in their breast milk 29 and an elevated milk Na/K ratio 23 , strongly suggesting breast dysfunction. In vitro studies determined T 288 S is mislocalized to the ER and lysosomes, and leads to accumulation of ER and lysosomal zinc, and activation of STAT3 signaling; however, the molecular and clinical implications of these observations are not currently understood.…”
Section: Discussionmentioning
confidence: 76%
“…Women who harbor T 288 S also have ~30% less zinc in their milk, concurrent with significantly elevated milk sodium levels 23 . Further characterization of T 288 S recently showed their milk also contains molecules indicative of increased oxidative and ER stress, and mammary gland remodeling 29 . Studies in vitro showed T 288 S is retained in the ER and lysosomes leading to zinc accumulation, ER and oxidative stress, and the activation of STAT3 signaling, a hallmark of mammary gland remodeling during involution 29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 15 16 ] Recently, Lee et al . [ 17 ] demonstrated that genetic variants in SLC30A2 (ZnT-2) mutation have profound consequences on zinc pools. This affects key cellular functions in mammary epithelial cells that may lead to breast dysfunction and decreased secretion of zinc into breast milk which otherwise contains adequate zinc for infantile requirements up to 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…In particular Lee et al., in 2018, studied SLC30A2 mutation in mice and demonstrated that genetic variants in ZnT2 may have profound consequences on Zinc pools affecting key cellular functions in MECs, which may lead to breast dysfunction and poor lactation performance in women …”
Section: Discussionmentioning
confidence: 99%